Prognosis of chronic hepatitis B transmitted from HBsAg positive mothers. Issue 2 (February 1987) - Bortolotti, F; Cadrobbi, P; Armigliato, M; Rude, L; Rugge, M; Realdi, G
Abstract : Nine children born to HBsAg positive mothers, who became chronic HBsAg carriers with associated liver disease, were followed for five to 10 years. Five children with active hepatitis or active cirrhosis at presentation achieved complete remission within six years, while three HBeAg positive patients with minimal histological lesions remained unchanged.